Bruce Bronzan Campaign Retreat at Morris Cabin-Shaver Lake - Watkins, Howard::::::::: (1978)
Bruce Bronzan, Linda Bronzan, Chloe Bronzan wearing Howard's long knitted green design cap, Christine Watkins Entry way to Bronzan home on Yosemite Ave., Fresno